Long-term impact of cadmium in protonema cultures of Physcomitrella patens - Kováčik, Jozef; Dresler, Sławomir; Babula, Petr (Ecotoxicology and environmental safety, 2020)
Antioxidative responses of axenic protonema cultures of the moss Physcomitrella patens exposed to 10 μM Cd over 40 d were studied. Cd treatment suppressed growth by ca. 75% with concomitant browning of some filaments and suppression of chlorophyll autofluorescence but had no impact on tissue water content. Despite this negative growth responses which could be related to enhanced ROS formation (as detected using fluorescence staining reagents for total ROS, hydroperoxides and lipid peroxidation), some metabolites revealed strong elevation by Cd which could contribute to attenuation of long-term Cd stress (elevation of ascorbic, malic and citric acids). Molar ratio of malate to Cd was 12.7 and citrate to Cd 2.5, thus potentially contributing to Cd chelation. Interestingly, GSH/GSSG pool and nitric oxide formation remained unaltered by Cd. Accumulation of Cd reached 82 μg/g DW with bioaccumulation factor of 73. Data indicate that Cd induces elevation of potentially protective metabolites even after prolonged exposure though they do not prevent oxidative stress sufficiently.
Keywords: reaktivní formy kyslíku; Bryopsida; chlorofyl; peroxidace lipidů; Cadmium; Hydrogen Peroxide; Oxidative Stress; peroxid vodíku; Antioxidants; Lipid Peroxidation; oxidační stres; Chlorophyll; kadmium; Reactive Oxygen Species; antioxidancia; mechy